Anaerobic speed reserve in young female rugby players: Methods and applications - Müller, C. B., Veiga, R. S.; Lopes, C. C.; Pinheiro, E. S.; Del Vecchio, F. B. (Science & Sports, 2022)
Introduction This study aimed to identify differences and concordances among anaerobic speed reserve calculated considering different tests of maximal sprint speed and aerobic fitness in young female athletes. Summary of facts and results Ten female rugby players (15.00 ± 0.21 years) performed sprint tests (20 m, 30 m and 40 m) to measure maximal sprint speed and aerobic tests to measure speed associate to maximum oxygen uptake, maximal aerobic speed and speed associated to intermittent fitness test. Nine combinations of anaerobic speed reserve were calculated. Anaerobic speed reserve using 20 m (speed associate to maximum oxygen uptake = 2.01 ± 0.59 m·s-1, maximal aerobic speed = 1.84 ± 0.59 m·s-1, speed associated to intermittent fitness test = 2.09 ± 0.46m·s-1) showed lower values when anaerobic speed reserve was determined with 30 m (speed associate to maximum oxygen uptake = 2.20 ± 0.63m·s-1, maximal aerobic speed = 2.03 ± 0.52 m·s-1, speed associated to intermittent fitness test = 2.28 ± 0.51 m·s-1; p = 0.009) and 40 m (speed associate to maximum oxygen uptake = 2.21 ± 0.60 m·s-1, maximal aerobic speed = 2.04 ± 0.48m·s-1, speed associated to intermittent fitness test = 2.29 ± 0.41 m·s-1; p = 0.037). Conclusion Also, the methods presented concordance among maximal sprint speed tests and aerobic tests. This suggests the viability of different tests to evaluate anaerobic speed reserve, and sprint tests of at least 30 m are more suitable for calculating anaerobic speed reserve.